Nursing students' evaluation of a gamified public health educational webinar: A comparative pilot study - Joseph Grech; Jessica Grech (Wiley, 2021)
Abstract Aim To compare undergraduate nursing students' evaluations of a gamified educational webinar to a non‐gamified version. Both webinars covered the topic "Determinants of health," part of public health education. Design A post‐test evaluation design with a comparison group, and an additional qualitative component. Methods First‐year students reading for a Bachelor of Science in Nursing at the Malta College of Arts, Science and Technology were randomly allocated into two classes of 26 students each, and to the gamified and non‐gamified webinars. The revised "Students Evaluations of Educational Quality" questionnaire was sent to all participants. Participants were also asked to provide comments on their learning experience. Results A total of 40 participants who attended the gamified and non‐gamified webinars completed the questionnaire. Educational quality was perceived as "good" to "very good," in both groups. Most participants in the gamified webinar group remarked that gamification helped to increase their engagement and interaction.